DInamika Identitas Betawi Kristiani di Kampung Sawah, Bekasi - Muhammad Agus Noorbani; Halimatusa'diah Halimatusa'diah (Universitas Andalas, 2022)
This paper presents the results of research on the Betawi Christian community in Kampung Sawah, Kota Bekasi. Based on interviews and literature study, this paper aims to analyze the dynamics of the identity of the people of Kampung Sawah and the acceptance of the Betawi Muslims towards them. The results of this study found that the Betawi identity continues to develop alongside the development of the residential area of this ethnic community and the flow of migration. The widespread motivation of scholars regarding the origins of the emergence of this ethnic group shows that this ethnic group is difficult to define as a result of the wide interaction between ethnic members and other ethnic groups. Because the identity of the Betawi is something that is fluid, the Betawi Christian of Kampung Sawah community can also be referred to as a part of the Betawi community. They shared Betawi identity and culture with other members of Betawi community as general.